2021
DOI: 10.1177/03010066211004055
|View full text |Cite
|
Sign up to set email alerts
|

Hot–Cold Confusion: Inverse Thermal Sensation When Hot and Cold Stimuli Coexist in a Thermal Localization Task

Abstract: We focused on the inverse thermal sensation caused by the presence of both hot and cold stimuli, which we named hot–cold confusion. Some researchers have shown that when participants touch a thermal stimulus simultaneously with two opposite thermal stimuli on both sides, the outer temperatures dominate the center temperature; for example, a hot stimulus between two cold stimuli is perceived as cold. However, there has not been sufficient research on the effect of the center stimulus on the outer stimuli. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The anecdotal feedback from participants during the current study supported the severity of the reported pain response when exposing the skin to capsaicin‐menthol cream, especially in the context of thermal challenge. This could be exacerbated by hot‐cold confusion, which is associated with an enhanced pain response (Arai et al, 2021). Unfortunately, we did not include an isolated capsaicin condition to clearly elucidate the responsible compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anecdotal feedback from participants during the current study supported the severity of the reported pain response when exposing the skin to capsaicin‐menthol cream, especially in the context of thermal challenge. This could be exacerbated by hot‐cold confusion, which is associated with an enhanced pain response (Arai et al, 2021). Unfortunately, we did not include an isolated capsaicin condition to clearly elucidate the responsible compounds.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of early thermal grill experiments (Thunberg, 1896), it is understood that simultaneous application of combined innocuous hot and cold stimuli can create illusionary hot pain. More recently, the related concept of hot-cold confusion has been recognised, which is characterised by an inverse thermal sensation (a misperception of temperature loci) when the limb's skin surface is presented with concurrent opposing temperature stimuli (Arai et al, 2021). In these experiments, Arai and colleagues demonstrated how hotcold confusion is often coupled with increased pain perception vs. singular hot or cold exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of the thermal sensation produced by the outer thermal stimuli being referred to as the central stimulation spot was termed as “domination” (Green, 1977b ). However, a more recent study by Arai et al ( 2021 ) challenged the “domination” hypothesis and introduced the concept of hot-cold confusion. In their first experiment, they presented three thermal stimuli in different patterns (alternate, adjacent, mixed, and same) of hot and cold to the forearm and observed that the participants sometimes perceived the inverse thermal sensation (cold perception of hot stimuli and vice-versa) of what was presented both at the center spot and the outer spots.…”
Section: Illusions Related To Body Spacementioning
confidence: 99%
“…In their first experiment, they presented three thermal stimuli in different patterns (alternate, adjacent, mixed, and same) of hot and cold to the forearm and observed that the participants sometimes perceived the inverse thermal sensation (cold perception of hot stimuli and vice-versa) of what was presented both at the center spot and the outer spots. Based on their findings, Arai et al ( 2021 ) hypothesized that there is a mutual effect between the hot and cold stimuli such that sometimes the outer stimulation influences the central stimulation and sometimes the reverse happens, and it did not matter which stimulus was greater in number. Moreover, the location (proximal or distal) of the thermal stimulus influenced the mutual effect.…”
Section: Illusions Related To Body Spacementioning
confidence: 99%
“…Ahmad et al also found that when multiple temperature stimuli are used to rapidly cool some of the actuators and slowly heat the rest, the slow-heating actuators are not perceived, suggesting that fast temperature changes are perceived at a much lower threshold than slow temperature changes, and that temperature perception is a non-linear phenomenon [ 13 ]. Arai et al found the inverse thermal sensation caused by the presence of hot and cold stimuli, which they called hot-cold confusion [ 14 ]. The opposite thermal stimuli applied at multiple locations affect each other, and participants sometimes perceive the hot stimulus at the outer location as cold even when the two of the three stimuli are hot, and vice versa.…”
Section: Introductionmentioning
confidence: 99%